2018
DOI: 10.3389/fenvs.2018.00140
|View full text |Cite
|
Sign up to set email alerts
|

Root Exudates Induce Soil Macroaggregation Facilitated by Fungi in Subsoil

Abstract: Subsoils are known to harbor large amounts of soil organic carbon (SOC) and may represent key global carbon (C) sinks given appropriate management. Although rhizodeposition is a major input pathway of organic matter to subsoils, little knowledge exists on C dynamics, particularly stabilization mechanisms, such as soil aggregation, in the rhizosphere of different soil depths. The aim of this study was to investigate the influence of natural and elevated root exudation on C allocation and aggregation in the tops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(90 citation statements)
references
References 88 publications
4
74
1
Order By: Relevance
“…Although recent research indicates that increasing root-C inputs can stimulate aggregation in deep soil layers (Baumert et al, 2018), the results of our physical fractionation indicate that integrating alfalfa into a cropping system has little impact on SOC stabilization through microaggregation. At Nashua and Marsden, the distribution of SOC among fractions was quite similar between cropping systems at all depths ( Figs.…”
Section: Values (Supplementarycontrasting
confidence: 80%
“…Although recent research indicates that increasing root-C inputs can stimulate aggregation in deep soil layers (Baumert et al, 2018), the results of our physical fractionation indicate that integrating alfalfa into a cropping system has little impact on SOC stabilization through microaggregation. At Nashua and Marsden, the distribution of SOC among fractions was quite similar between cropping systems at all depths ( Figs.…”
Section: Values (Supplementarycontrasting
confidence: 80%
“…Our results confirmed that microbial variables had greater impact on SOC in > 0.25 mm macro-aggregates under different fertilizations, whereas no significant effect was found in < 0.25 mm micro-aggregates. The total effect of fungi-related indicators contribution was higher than other microbial indices 77 . More in-depth studies are needed to detect fungal reaction and variation resulting from fertilization and should be incorporated in the main causes of microbial approach that affect C stock.…”
Section: Discussionmentioning
confidence: 64%
“…The aggregated structure of soil is stabilized by microbial exudation of hydrophobic extracellular proteins and polysaccharides (e.g. Baumert et al., 2018; Chenu & Cosentino, 2011; Hallett & Young, 1999) and enmeshment by fungal hyphae (Chenu & Cosentino, 2011).…”
Section: Biological Agents Of Soil Structure Dynamicsmentioning
confidence: 99%